ANALYSIS OF THE DEVELOPMENT OF STRUCTURAL COMPONENTS OF VISUAL THINKING IN ADOLESCENTS STUDYING MATHEMATICAL PROFILE (Pedagogy of Higher and Secondary Education, 2022)
The article presents some peculiarities development structure components of visual thinking peculiarities of its development in juveniles which training in mathematical profiles classes.
Keywords: visual thinking; profile training; mathematical profile classes